DESAIN WEB BASED LEARNING PADA SMA NEGERI I DAMPIT MENGGUNAKAN PHP DENGAN DATABASE MYSQL - Sundari, Retno; Wasono, Hendrik Tri (DINAMIKA DOTCOM, 2013)
State High School is a school located Dampit dikabupaten poor, who continue to make good progress infrastructure to improve the learning process of students.The development that made high school Dampit School I intend to utilize the Internet as an alternative medium of On-line learning.System of On-line learning with a concept and mechanism of teaching and learning (education) based IT (information technology). This concept is known as e-Learning. With e-Learning brings the influence of the process of transformation of conventional education into digital form, both the content (contents) and the system. It is very interesting for the author to be used as Scientific Research. This analysis aims to add conditions the On-line learning is not limited by distance, time and place of learning.From the results of analyzes obtained that the On-line learning will accelerate transfer of knowledge and information. With the online-based system is then expected will be easier in the learning process is right on target according to what is desired.Â Key words : Web Based Learning, High School School I Dampit